Surface-treated copper foil having columnar mass structure, copper-clad laminate comprising same, and printed wiring board
By electroplating the copper foil surface to form a clump structure, the problem of insufficient adhesion strength of copper foil in high-frequency signal transmission is solved, and high adhesion strength and suitable for high-frequency signal transmission is achieved.
Patent Information
- Application Number
- CN202380059362.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-07-31
- Publication Date
- 2025-03-14
AI Technical Summary
The existing copper foils have insufficient adhesion strength in high-frequency signal transmission, especially on printed wiring boards using liquid crystal polymers (LCP), and excessive surface treatment will increase interference factors in high-frequency signal transmission.
通过对生铜箔表面进行电镀处理形成团块结构的表面,包括柱部和分支部,且控制表面粗糙度在1.0 um或更小,优选为0.7 um或更小。
Copper foil with high adhesion strength to printed circuit boards is realized, suitable for high-frequency signal transmission, and significantly improves adhesion to LCP resin.
Smart Images

Figure CN119630839A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a surface-treated copper foil, and more particularly to a surface-treated copper foil having excellent adhesion to a resin substrate and suitable for application as a high-frequency foil, a copper-clad laminate including the copper foil, and a printed wiring board. Background Art
[0002] As miniaturization and weight reduction of electrical / electronic devices accelerate, printed circuits formed on substrates have become more complex, more highly integrated, and more miniaturized, so that copper foils used in printed circuit boards are required to have various properties.
[0003] Composite materials for use in boards for manufacturing flexible boards, multilayer boards for high-density mounting, high-frequency circuit boards, and the like for electrical / electronic devices (hereinafter, such board systems are referred to as "circuit boards" or "printed wiring boards") are composed of conductors (copper foils) and insulating substrates (including films) supporting the conductors, and the insulating substrates ensure insulation between the conductors and have sufficient strength to support the components.
[0004] In the past, in order to enhance the adhesion strength to the insulating substrate, the 10-point average roughness Rz was increased by amplifying the current flowing during surface treatment and increasing the amount of granular copper deposited during surface treatment. However, this method is suitable as a method for enhancing adhesion strength, but is not suitable for circuit boards considering high-frequency characteristics, because excessive treatment of the copper foil surface for enhancing the adhesion strength signal increases the interference factor of high-frequency signal transmission, which has an adverse effect on transmission.
[0005] In recent years, in the 5G high-frequency environment, data transmission speeds have increased 100 times or more. In the case of printed wiring boards used for high-frequency and high-speed transmission in the 5G environment, the market for printed circuit boards using low-loss, ultra-fine, high-density liquid crystal polymers (LCP) is growing rapidly. LCP has a coefficient of thermal expansion (CTE) similar to that of copper; it has excellent impact resistance and will not break due to external shock or vibration; and in terms of moisture resistance, it has excellent moisture resistance properties compared to polyimide (PI) in high-frequency environments. However, existing LCPs, similar to low dielectric loss resins or other thermosetting resins, have problems such as poor adhesion and heat resistance, as well as poor adhesion and processability to copper foil. Summary of the invention
[0006] 1. Technical issues to be resolved
[0007] The present invention aims to solve the above-mentioned problems, and an object of the present invention is to provide a surface-treated copper foil having high adhesive strength to a printed wiring board and having a novel surface structure, a copper-clad laminate including the copper foil, and a printed wiring board including the copper foil.
[0008] An object of the present invention is to provide a surface-treated copper foil having a surface roughness suitable for high-frequency signal transmission, a copper-clad laminate including the copper foil, and a printed wiring board including the copper foil.
[0009] An object of the present invention is to provide a surface-treated copper foil having high adhesive strength to a printed wiring board using a liquid crystal polymer (LCP), a copper-clad laminate including the copper foil, and a printed wiring board including the copper foil.
[0010] (II) Technical solution
[0011] To solve the above technical problems, the present invention provides a surface-treated copper foil, comprising a surface-treated surface formed by surface treatment of a raw foil, wherein the surface-treated copper foil comprises a plurality of cluster structures, and the plurality of cluster structures are formed on the surface-treated surface, wherein the cluster structures comprise: a column portion extending from the surface of the surface-treated copper foil; and a branch portion extending from a side surface or an end portion of the column portion, and wherein the surface-treated surface has a surface roughness (Rz) of 1.0 um or less.
[0012] In the present invention, the surface roughness (Rz) of the surface treated is preferably 0.7 um or less.
[0013] In addition, the width (w) of the cluster structure is preferably 400 nm or less, and the ratio (h / w) of the height (h) to the width (w) of the cluster structure is preferably greater than 1. In addition, the ratio (h / w) of the height (h) to the width (w) of the cluster structure may be 1.2 or greater.
[0014] In the present invention, the width (w) of the cluster structure may be 130 to 350 nm; the height (h) of the cluster structure may be 300 to 550 nm; and the distance (d) between the cluster structures may be 200 nm or more. Preferably, the distance (d) between the cluster structures may be 250 to 600 nm.
[0015] In the present invention, the density of the agglomerate structure may be 2 to 20 / µm 2 .
[0016] In the present invention, the surface-treated surface of the surface-treated copper foil may have a glossiness of less than 10.
[0017] To solve another technical problem, the present invention provides a copper-clad laminate, which includes the surface-treated copper foil laminated on a resin substrate. In this case, the resin substrate may include an LCP resin.
[0018] (III) Beneficial effects
[0019] According to the present invention, a surface-treated copper foil having a novel surface structure and having high adhesion strength to a printed circuit board can be provided. In addition, according to the present invention, a surface-treated copper foil having a surface roughness suitable for high-frequency signal transmission and having high adhesion strength to a printed circuit board using a liquid crystal polymer (LCP) can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a schematic diagram of a cluster structure on the surface of a copper foil according to an embodiment of the present invention.
[0021] Figures 2 to 4 1 and 2 are scanning electron microscope images of the surfaces of the surface-treated copper foils prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention, respectively.
[0022] Figure 5a and Figure 5b 1 is an image of the surface of the LCP resin after the surface-treated copper foil prepared in the examples of the present invention and the comparative examples was attached to the LCP resin and then the copper foil was removed by complete etching.
[0023] Figure 6 : is a graph showing the XPS analysis results of samples before and after the adhesion strength measurement of the surface-treated copper foil prepared in Examples of the present invention. Best Mode for Carrying Out the Invention
[0024] The embodiments described in this specification and the configurations described in the drawings are only the most preferred embodiments of the present invention, but do not represent all the technical ideas of the present invention, and therefore the present invention may include various equivalents and modifications that can replace the exemplary embodiments when applying for the present application. Hereinafter, the embodiments of the present invention will be described in more detail with reference to the accompanying drawings.
[0025] Herein, unless otherwise specified, factor values representing dimensions, such as width, height, and length of a structure, or measured values of a feature of a structure, indicate average values.
[0026] The surface-treated copper foil of the present invention includes a raw foil and a surface-treated layer on at least one surface of the raw foil. In the present invention, the surface-treated layer may include a roughening layer and an anti-oxidation layer, and may further include a chromate layer or an additional layer.
[0027] Hereinafter, the green foil, the roughened layer, and the anti-oxidation layer of the present invention will be described in detail.
[0028] A. Raw Foil
[0029] In the present invention, a known copper foil may be used as the raw copper foil, but is not limited thereto. According to an embodiment, the untreated copper foil may be an electroplated copper foil or a rolled copper foil.
[0030] In the present invention, the thickness of the raw foil is not particularly limited, but when the surface-treated copper foil is used for a printed wiring board, the thickness of the raw foil may be, for example, 6 to 35 µm, and preferably 6 to 18 µm.
[0031] In the present invention, in the case of electroplated foil, the surface roughness Rz of the deposition side of the raw foil may be 0.7 μm, more preferably 0.65 μm or less, 0.6 μm or less, 0.5 μm or less, or 0.45 μm or less. In the present invention, the raw foil has a tensile strength of preferably 40 kgf / mm 2 Up to 70 kgf / mm 2 .
[0032] In the present invention, the mechanical properties of the green foil preferably remain uniform before and after hot pressing during bonding with a preform for molding a copper clad laminate or a printed wiring board. In the present invention, the green foil has minimal variation in crystal grains before and after pressing.
[0033] B. Roughening layer
[0034] In the present invention, the roughened layer may be formed on one surface or both surfaces of the raw foil. The surface treated layer of the present invention may be formed by electroplating the raw foil.
[0035] As the electrolyte, an aqueous solution having a pH of 1 to 8 (e.g., 6 to 7) may be used, which contains 10 to 90 g / L of a copper salt, 30 to 150 g / L of sulfuric acid, 0.1 to 0.5 g / L of cobalt, 0.2 to 2 g / L of tungsten, and 0.2 to 2 g / L of titanium. Examples of the copper salt may include copper sulfate (CuSO4), copper nitrate (Cu(NO3)2), copper chloride (CuCl2), and copper acetate (Cu(CH3COO)2).
[0036] Electroplating can be performed, for example, by using an insoluble electrode as a cathode and an untreated green foil as an anode, while immersing the green foil in an electrolyte at a solution temperature of 25° C. to 45° C. and 16 to 20 A / dm 2 The current density is for example 5 to 15 seconds, but is not limited thereto.
[0037] C. Antioxidant layer
[0038] Additionally, in the present invention, an anti-oxidation layer may be formed on the surface-treated layer. The anti-oxidation layer may contain nickel (Ni) and phosphorus (P). In addition to nickel and phosphorus, the anti-oxidation layer may further contain zinc (Zn), cobalt (Co), titanium (Ti), tin (Sn), and the like.
[0039] The amount of the anti-oxidation layer deposited may be, for example, 30 to 300 mg / m 2 , or as another example, 50 to 120 mg / m 2 , but not limited to this.
[0040] In the present invention, the method of forming the antioxidant is not particularly limited. Illustratively, the antioxidant can be formed by reacting the nickel salt in an aqueous solution containing 3 to 10 g / L of a nickel salt and 15 to 40 g / L of phosphoric acid (H3PO4) at a solution temperature of 25°C, a pH of 2 to 4, and an A / dm 2 The electroplating was performed at a current density of 1 A / dm for 1 to 3 seconds, followed by electroplating in an aqueous solution containing 3 to 10 g / L of zinc and having a pH of 1 to 3 at 1 A / dm 2 The current density is electroplated for 2 to 4 seconds.
[0041] Specifically, examples of nickel salts may include nickel sulfate (NiSO 4 ), nickel nitrate (Ni(NO 3 ) 2 ), nickel chloride (NiCl 2 ), nickel acetate (C 4 H 6 NiO 4 ), and the like, but are not limited thereto.
[0042] A chromate layer may be additionally formed on the anti-oxidation layer. The chromate layer may be formed by reacting an aqueous solution having a chromic anhydride concentration of 3 to 7 g / L at room temperature, pH 5.0, and 0.5 A / dm 2 The current density is treated for 4 seconds to form.
[0043] The silane coupling agent layer may be formed on the copper foil having the anti-oxidation layer by immersing in an aqueous solution having a silane coupling agent concentration of 1 to 10 g / L at room temperature and pH 3 to 5 for 2 to 4 seconds.
[0044] The surface-treated copper foil of the present invention surface-treated by the above method includes a lump structure having a column shape extending in a direction perpendicular to the surface of the copper foil.
[0045] Figure 1 is a schematic diagram of a cluster structure on the surface of a copper foil according to an embodiment of the present invention.
[0046] The cluster structure of the present invention has a needle-like column shape extending in a direction substantially perpendicular to the surface of the copper foil (forming an angle of 60 to 90 degrees relative to the surface of the copper foil). However, the cluster structure of the present invention is characterized in that it includes a branch structure from the side surface or end of the pillar structure.
[0047] Specifically, refer to Figure 1 , each cluster structure 100 of the present invention may include: a column portion 100A, which extends in a direction substantially perpendicular to the copper foil surface S and forms a body; and a branch portion 100B, which branches from the side surface or the upper surface of the column portion. In the present invention, the column portion and the branch portion constituting the cluster structure may be separate clusters or particles, or the column portion and the branch portion may each be an assembly or aggregation of a plurality of clusters or particles, but is not limited thereto, and alternatively, the entire cluster structure may include one cluster or particle.
[0048] In the present invention, the agglomerate structure has a needle-like or columnar structure whose aspect ratio, which represents the ratio of the height (h) to the width (w) of the structure, exceeds 1. The aspect ratio (h / w) of the agglomerate structure may preferably be 1.2 or more, 1.4 or more, 1.5 or more, or 1.6 or more, and the aspect ratio is preferably 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, or 2.0 or less.
[0049] In the present invention, the width (w) of the cluster structure may be 400 nm or less, preferably 130 to 350 nm. The height (h) of the cluster structure may be 600 nm or less, preferably 300 to 550 nm.
[0050] Specifically, the width (w) of the cluster structure is defined as the maximum value among the width values measured on the cross section cut in the direction parallel to the copper foil surface at any position of the cluster structure, and the height (h) of the cluster structure is defined as the maximum value among the height values measured on the cross section cut in the direction perpendicular to the copper foil surface at any position of the cluster structure. It will be understood that the size (width or height) of the column and branch portions constituting the cluster structure can be measured in the same manner as the width or height of the cluster structure described above.
[0051] In the present invention, the cluster structures are discretely distributed on the copper foil surface. The distribution pattern of the cluster structures has no particular rule, but the distance d between the cluster structures may be 200 nm or more, preferably in the range of 250 to 600 nm.
[0052] The degree of dispersion in the surface-treated copper foil of the present invention can be expressed as the number of agglomerate structures per unit area. Illustratively, the density of agglomerate structures can be 2 to 20 / µm 2 , 3 to 15 / µm 2 , 5 to 15 / µm 2 , or 5 to 10 / µm 2. Different from this, the degree of discreteness of the agglomerate structure of the present invention can be expressed as the ratio of the distance d to the width w of the agglomerate structure. For example, the distance d may preferably have a value greater than the width w in the agglomerate structure of the present invention. Illustratively, the ratio of the distance d to the width w of the agglomerate structure may be 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 4.0 or less, 3.5 or less, 3.0 or less, 2.5 or less, or 2.0 or less.
[0053] As shown, in the agglomerate structure of the present invention, the width and length of the branch portion are generally smaller than the width and height of the pillar portion. However, in the present invention, the branch portion refers to a structure having a width or height of at least a predetermined value, such as at least 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm.
[0054] The surface-treated copper foil of the present invention exhibits high adhesive strength when attached to a resin substrate. This is assumed to be due to the anchoring effect generated by the mass structure including the pillar portion and the branch portion.
[0055] Additionally, the surface-treated copper foil of the present invention has a very low 10-point average roughness (Rz) value while exhibiting high adhesion strength to the resin substrate. Despite the high aspect ratio of the agglomerate structure, the surface-treated copper foil of the present invention may have a 10-point average roughness value of 1.0 µm or less, 0.9 µm or less, 0.8 µm or less, 0.7 µm or less, or 0.6 µm or less, or 0.5 µm or less. The 10-point average roughness Rz of the surface-treated copper foil of the present invention may be 0.2 µm or greater, or 0.3 µm or greater. The term "10-point mean roughness Rz" refers to the 10-point average roughness Rz specified in the definition of 5.1 ten-point average roughness in JIS B 0601-1994 "Definition and indication of surface roughness".
[0056] Therefore, the surface-treated copper foil of the present invention can be applied to a circuit board considering high-frequency characteristics, and can show high adhesion characteristics even to an LCP polymer.
[0057] In the present invention, the surface-treated copper foil can be attached to a low dielectric resin, polyimide, hydrocarbon, polytetrafluoroethylene film, or LCP resin to manufacture a copper-clad laminate. The surface-treated copper foil of the present invention can have an adhesion strength of 0.7 kgf / cm or more relative to the low dielectric resin, polyimide, hydrocarbon, polytetrafluoroethylene film, or LCP. The adhesion strength can be the adhesion strength measured according to the JIS C6481 standard.
[0058] The above-mentioned surface-treated copper foil laminated on a resin substrate can be used as a copper-clad laminate, and this copper-clad laminate can be used to produce a printed wiring board. DETAILED DESCRIPTION
[0059] Hereinafter, the present invention will be described in detail with reference to examples. However, these examples are shown in an illustrative manner and should not be construed as limiting the present invention in any way.
[0060] <Example 1>
[0061] In order to prepare copper foil by electroplating, a 2-L volume electrolysis system capable of circulating at 20 L / min was prepared. Specifically, the temperature of the copper electrolyte was constantly maintained at 45°C. A dimensionally stable electrode (DSE) electrode plate with a thickness of 10 mm and a size of 10 cm × 10 cm was used as the cathode, and a titanium electrode plate with the same size and thickness as the cathode was used as the anode.
[0062] As the green foil, a fabric (product name: I2S, from ILJIN Materials) having a roughness (Rz) of 0.43 µm and a thickness of 12 µm was used.
[0063] The roughening layer was prepared by using an aqueous solution of pH 6 to 7 containing 30 g / L of copper salt (copper sulfate), 90 g / L of sulfuric acid, 0.3 g / L of cobalt, 0.8 g / L of tungsten, and 0.6 g / L of titanium as the electrolyte at a solution temperature of 45°C and a current of 16 to 20 A / dm 2 The current density is electroplated for 6 seconds.
[0064] Next, the anti-oxidation layer was prepared by heating the solution in an aqueous solution containing 5 g / L nickel salt and 20 g / L phosphoric acid (H3PO4) at a temperature of 25°C, a pH of 2 to 4, and a pressure of 1 A / dm 2 The electroplating was carried out at a current density of 1 A / dm for 1 to 3 seconds, and in an aqueous solution containing 5 g / L zinc and having a pH of 1 to 3, the electroplating was carried out at a current density of 1 A / dm 2 The current density is electroplated for 2 to 4 seconds.
[0065] Next, the chromate layer was placed in an aqueous solution having a chromic anhydride concentration of 5 g / L at room temperature, pH 5.0, and 0.5 A / dm 2 It is formed under the conditions of current density and processing time of 4 seconds.
[0066] The copper foil having the chromate layer was immersed in a solution of 1 to 10 g / L of a silane coupling agent for 3 seconds, and then dried using hot air at a temperature of 100° C., thereby preparing a surface-treated copper foil.
[0067] <Example 2>
[0068] A roughened layer, an anti-oxidation layer, a chromate layer, and a silane coupling agent layer were formed by the same method as in Example 1, except that a fabric having a roughness (Rz) of 0.61 µm (product name: I2S, available from ILJIN Materials) was used as the raw foil.
[0069] <Comparative Example 1>
[0070] Similar to Example 1, a fabric (product name: I2S) having a roughness (Rz) of 0.43 µm and a thickness of 12 µm was used as a raw foil. The roughened layer was formed by heating the raw foil at a solution temperature of 45°C and a pressure of 7 to 12 A / dm while using an aqueous solution containing 50 g / L of copper sulfate and 100 g / L of sulfuric acid at a pH of 3.5 to 5.5. 2 The current density is electroplated for 8 seconds.
[0071] Next, an anti-oxidation layer, a chromate layer, and a silane coupling agent layer were formed under the same conditions as in Example 1.
[0072] <Comparative Example 2>
[0073] Similar to Example 1, a fabric (product name: I2S) having a roughness (Rz) of 0.43 µm and a thickness of 12 µm was used as a raw foil. The main roughening layer was formed by using an aqueous solution containing 50 g / L of copper sulfate and 100 g / L of sulfuric acid at a solution temperature of 45°C and a pressure of 6 to 11 A / dm 2 Next, the secondary roughening layer was formed by electroplating at a current density of 1 to 3 for 4 seconds using an aqueous solution containing 250 g / L of copper sulfate and 100 g / L of sulfuric acid at a solution temperature of 45°C and a current density of 10 to 14 A / dm 2 The current density is electroplated for 4 seconds twice.
[0074] Next, an anti-oxidation layer, a chromate layer, and a silane coupling agent layer were formed under the same conditions as in Example 1.
[0075] <Property Assessment>
[0076] Regarding properties, each of the surface-treated copper foil samples prepared in Examples and Comparative Examples was measured. The property evaluation items and measurement methods are as follows.
[0077] a. 10-point average roughness R z (Unit: µm)
[0078] 10-point average roughness R of copper foil after surface treatment z Measured using a surface roughness meter according to JIS B0601 standard.
[0079] b. Agglomerate particle size, agglomerate distance, and agglomerate density
[0080] A SEM image of the surface of the copper foil after the surface treatment was taken using a scanning electron microscope, and the particle diameters of 100 agglomerate structures within an area of 100 µm × 100 µm were measured, and the average value thereof was obtained. Similarly, the distance between any agglomerates within an area of 100 µm × 100 µm on the SEM image was measured at 100 points.
[0081] The density of clusters (# / µm) was obtained by counting the number of clusters in an area of 1 µm × 1 µm on the SEM image of the copper foil surface. 2 ).
[0082] c. Adhesion strength (unit: kgf / cm)
[0083] The samples were prepared by preparing an LCP resin (manufacturer: COPOLYMEN®) having a thickness of 50 µm and pressing the surface-treated copper foil samples of Examples 1 and 2 and Comparative Examples 1 and 2 having a width of 10 mm on the LCP resin, respectively. The pressing conditions were a temperature of 350°C, a pressure of -1.8 MPa, and 5 minutes. The prepared test samples were measured for adhesive strength by a 90° peeling method according to JIS C 64718.1.
[0084] d. Glossiness (Gs 60°)
[0085] The glossiness of the surface of the copper foil after the surface treatment was measured according to JIS Z 8741 standard.
[0086] e. Color difference measurement
[0087] A colorimeter (manufacturer: KONICA MINOLTA) was prepared, and after the surface treatment of the copper foil, the L*, a*, and b* values of the surface of the copper foil were measured by a specular component excluded (SCE) method.
[0088] Figures 2 to 4 1 and 2 are electron microscope images of the surfaces of the surface-treated copper foils prepared in Example 1, Comparative Example 1, and Comparative Example 2. Blocks (a) and (b) in each figure show images with different magnifications.
[0089] like Figure 2 As shown, the surface-treated copper foil prepared in Example 1 includes needle-like columnar agglomerate structures extending at an angle of 60 to 90 degrees relative to the surface of the copper foil, such as Figure 1 Most of the mass structures include a plurality of branches branching from the side surface or end of the column. These structures are significantly different from Figure 3 and Figure 4 The cluster structure shown in .
[0090] The width and height of the agglomerate structures and the distances between the agglomerate structures on the electron microscope image were measured at different positions of the sample of Example 1, and the average values of each round of measurement are shown in Table 1 below.
[0091] [Table 1]
[0092]
[0093] The measured cluster width had a minimum of 138 nm and a maximum of 313 nm; the measured cluster height had a minimum of 282 nm and a maximum of 529 nm; and the measured cluster distance had a minimum of 260 nm and a maximum of 567 nm. The cluster density at each measurement location was 3 to 12 / µm 2 .
[0094] Table 2 below shows a summary of the property evaluation results.
[0095] [Table 2]
[0096]
[0097] Referring to Table 2, despite the low surface roughness, the samples of Example 1 and Example 2 still showed high adhesive strength.
[0098] Figure 5a and Figure 5b The images are of the surface of the LCP resin after the surface-treated copper foil prepared in Example 1 and Comparative Example 2 is attached to the LCP resin and then the copper foil is completely removed by etching.
[0099] Reference Figure 5a , the cluster structure according to the example of the present invention has a high aspect ratio and a branched structure, and therefore, an adhesive surface having a complex shape is formed between the copper foil and the LCP resin, resulting in a strong bonding therebetween.
[0100] Figure 6The graph is a graph showing the XPS analysis results of the surface-treated copper foil prepared in Example 1 before and after the adhesion strength measurement. In the graph, "LCP" and "Cu" indicate the XPS analysis data before the LCP resin is attached to the surface-treated copper foil, and "P / S: 1.1" indicates the XPS analysis data of the surface of the copper foil after the adhesion strength measurement of the surface-treated copper foil sample prepared in Example 1.
[0101] Reference Figure 6 After measuring the adhesion strength, the surface of the copper foil is 1s Peak (P / S: 1.1) and LPS O 1s These results confirm that transgranular fracture is accompanied in LCP when measuring adhesion strength, and the resin transgranular fracture mechanism indicates that high adhesion strength is formed at the interface between the surface-treated copper foil and the resin of the copper-clad laminate.
[0102] Although the preferred embodiments of the present invention have been described in detail, it should be understood that various modifications may be made to the embodiments by a person skilled in the art without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited by the embodiments, but should be limited by the scope of the following claims and their equivalents.
[0103] Industrial Applicability
[0104] The present invention can be applied to copper foil, copper-clad laminates, and printed wiring boards.
Claims
1. A surface-treated copper foil comprising a surface-treated surface formed by surface treatment of a raw foil, characterized in that: The surface-treated copper foil includes a plurality of mass structures, wherein the plurality of mass structures are formed on the surface treated surface. The mass structure comprises: A column portion extending from a surface of the surface-treated copper foil; and a branch portion extending from a side surface or an end of the column portion, and The surface treated has a surface roughness of 1.0 um or less.
2. The surface-treated copper foil according to claim 1, wherein The surface roughness of the surface treated is 0.7 um or less.
3. The surface-treated copper foil according to claim 1, wherein: The width (w) of the cluster structure is 400 nm or less, and the ratio (h / w) of the height (h) to the width (w) of the cluster structure exceeds 1.
4. The surface-treated copper foil according to claim 3, wherein: The ratio (h / w) of the height (h) to the width (w) of the agglomerate structure is 1.2 or greater.
5. The surface-treated copper foil according to claim 3, wherein: The width (w) of the cluster structure is 130 to 350 nm.
6. The surface-treated copper foil according to claim 3, wherein: The height (h) of the cluster structure is 300 to 550 nm.
7. The surface-treated copper foil according to claim 3, wherein: The distance (d) between the cluster structures is 200 nm or more.
8. The surface-treated copper foil according to claim 7, wherein: The distance (d) between the cluster structures is 250 to 600 nm.
9. The surface-treated copper foil according to claim 1, wherein: The density of the agglomerate structure is 2 to 20 / µm 2 .
10. The surface-treated copper foil according to claim 1, wherein: The surface treated copper foil has a glossiness of less than 10.
11. A copper-clad laminate, characterized in that: The surface-treated copper foil according to any one of claims 1 to 10 is laminated on a resin substrate.
12. The copper-clad laminate according to claim 11, characterized in that The resin matrix includes LCP resin.